Trends in Ethnomathematics Research Through Traditional Dance for Primary Mathematics Education: A Bibliometric Analysis - Setiyadi, Desi; Zaenuri, Zaenuri; Trimurtini, Trimurtini (Proceedings of International Conference on Science, Education, and Technology, 2025)
The integration of ethnomathematics rooted in traditional dance into primary school mathematics instruction plays a vital role in connecting students with their cultural heritage while enhancing the relevance of education. This study aims to: (1) analyze the trends and patterns of research related to traditional dance-based ethnomathematics in primary mathematics education; (2) examine various aspects such as annual publication rates, institutional collaborations, and the most frequently used keywords over the past ten years; and (3) identify future research opportunities in the field of ethnomathematics. The method employed is bibliometric analysis, which involves collecting and evaluating data from scientific publications indexed in Scopus from 2016 to 2025. The analysis focuses on citation patterns, author collaborations, and keyword trends. The results reveal a total of 243 scientific documents addressing topics related to ethnomathematics and traditional dance, with an annual publication growth rate of 3.51%. The average number of citations per document stands at 7.741, indicating significant interest from the academic community. This approach has proven effective in enhancing student motivation and engagement cognitively, emotionally, and kinesthetically while also strengthening their cultural identity. The study recommends the development of curricula that prioritize local values and encourage collaboration among academics, educators, and communities. Thus, integrating ethnomathematics into education serves not only as a pedagogical solution but also as a cultural strategy to reinforce national identity in the face of globalization, while equipping the younger generation with stronger critical and creative thinking skills.